2008
DOI: 10.1097/dmp.0b013e31818aaf55
|View full text |Cite
|
Sign up to set email alerts
|

Hurricane Katrina Deaths, Louisiana, 2005

Abstract: Hurricane Katrina was the deadliest hurricane to strike the US Gulf Coast since 1928. Drowning was the major cause of death and people 75 years old and older were the most affected population cohort. Future disaster preparedness efforts must focus on evacuating and caring for vulnerable populations, including those in hospitals, long-term care facilities, and personal residences. Improving mortality reporting timeliness will enable response teams to provide appropriate interventions to these populations and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
168
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(174 citation statements)
references
References 2 publications
5
168
0
1
Order By: Relevance
“…In addition to increased injuries, hurricanes also frequently result in mortality. [12][13][14][15] Active mortality surveillance not only provides robust data, but it also provides timely information regarding the number and characterization of deaths during a disaster. Texas's active surveillance system is one of the few existing active mortality surveillance systems 4 that are designed to assess hurricane-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increased injuries, hurricanes also frequently result in mortality. [12][13][14][15] Active mortality surveillance not only provides robust data, but it also provides timely information regarding the number and characterization of deaths during a disaster. Texas's active surveillance system is one of the few existing active mortality surveillance systems 4 that are designed to assess hurricane-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…(Brunkard et al 2008, Jonkman et al 2009). The latest NHC estimate is that Katrina was directly responsible for about 1200 deaths and it remains the third deadliest hurricane to strike the United States.…”
Section: Faq Part Imentioning
confidence: 99%
“…While most studies have found that the elderly are more vulnerable to floods (Jonkman et al 2009;Myung and Jang 2011;Thacker et al 2008), it has also been reported that very young children, especially in low-income countries, have higher flood-related mortality (Pradhan et al 2007). Similarly, for storm-related deaths, both children and older adults are exposed disproportionately to higher mortality risks (Brunkard et al 2008;Bern et al 1993;Chowdhury et al 1993). With respect to gender, in developed countries men are generally more likely to die from flood-and storm-related causes, whereas in less developed countries women appear to have a higher risk of mortality (Alderman et al 2012;Doocy et al 2013aDoocy et al , 2013b.…”
Section: Introductionmentioning
confidence: 99%